The effects of 3D multi-user virtual environments on freshmen university students' conceptual and spatial learning and presence in departmental orientation - Tuezuen, Hakan; Oezdinc, Fatih (Computers and education, 2016)
The purpose of this study was to examine the usefulness of 3D multi-user virtual environments (MUVEs) for freshmen orientation purposes. To do so, a virtual orientation environment was developed on the Active Worlds MUVE. The study sample included 55 students who were enrolled in a university department. The study has a quasi-experimental control group design. The orientation was carried out a week before the academic semester. The virtual departmental orientation was conducted with 25 participants in the 3D MUVE, while the authentic departmental orientation was conducted with 30 participants who were led through the department by a guide. Both groups were administered a Conceptual Knowledge Test before and after their orientations along with a Spatial Knowledge Inventory and an Orientation Evaluation Questionnaire after the interventions. In addition, the Presence Questionnaire in Virtual Environments was administered to the virtual orientation participants. While the conceptual knowledge posttest scores of experimental and control groups increased significantly, there was no significant difference between them. It was found that students in the virtual orientation recalled spatial route details better than the participants in the authentic orientation, while there was no significant difference between the groups in terms of spatial landmark details and overall spatial scores. When the groups were compared in terms of evaluation factors, significant differences were observed in the effect on general learning and simplicity in favor of the virtual orientation, while there were no significant differences in perceived usefulness and enjoyment. Participants perceived a high level of presence in the virtual orientation. There was a small positive correlation between presence and conceptual knowledge and a moderate positive correlation between presence and spatial knowledge. Decreasing distraction factors in the virtual environment had a positive influence on students' conceptual and spatial learning. In general, the virtual orientation has similar or better results than authentic orientation in terms of the variables examined in this study. These findings demonstrate that 3D MUVEs can be effectively used by freshmen students for orientation purposes. •We examine the usefulness of 3D MUVEs for freshmen orientation purposes.•Conceptual knowledge increased significantly in virtual and authentic orientations.•Virtual orientation participants recalled spatial route details better.•Decreasing distraction in virtual space increases conceptual and spatial learning.•Virtual orientation has similar or better results than authentic orientation.